KOMPETENSI SISWA TENTANG KEBENCANAAN DALAM PEMBELAJARAN AL-QUR’AN - Irfan Afandi (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
Disaster learning becomes very important for students to provide students' competence in dealing with disasters. The earth, which has experienced extreme climate change in recent decades and the geographical condition of Indonesia, which is in the ring of fire, makes it necessary to introduce disaster preparedness to students. Al-Qur'an learning that teaches understanding of the holy book can participate in equipping students in dealing with disasters. Students' competence in learning the Qur'an is found in the verses of the Qur'an about disasters. Education in al-Qur'an learning can lead to students' spiritual competence, including understanding and awareness that disasters have been written in the mahfudz lauh, disasters have been ordained by Allah SWT. Disaster itself actually comes from human error in managing the environment. More than that, learning the Qur'an also provides an understanding of the nature of patience in dealing with disasters. Patience competence provides students with provisions to survive in the face of disasters; In addition, the verses of the Qur'an also teach about 'repentance' or returning to protecting the environment so that disasters that originate from human error in managing the environment will not be repeated again. Damages on earth can be minimized if humans want to repent. In addition, students also get the competence to identify disasters that will be experienced. There are 5 (five) disasters identified by Qs. al-Baqoroh namely fear, hunger, lack of wealth, lack of life (death / health) and lack of fruit (basic food needs).